Restructuring The Performance Management of Security Service Enterprises (BUJP) Through The Balanced Scorecard Approach: A Critical Analysis of Strategies to Mitigate Staff Turnover and Enhance Operational Discipline at PT Gitra Sandi Borlak - Dimas Kuncoro Yekti; Olivia Tiara; Cedaryana Cedaryana (Publikasi Indonesia, 2026)
The security outsourcing industry in Indonesia faces persistent challenges including high employee turnover, field discipline issues, and demanding SLA fulfillment for personnel substitution. PT Gitra Sandi Borlak, a strategic Security Services Business Entity (BUJP) managing security portfolios in healthcare and manufacturing sectors, has experienced significant business growth yet continues to receive recurring client complaints regarding personnel instability and operational discipline. This research aims to formulate a reconstruction of the performance management system in Security Services Business Entities (BUJP), with an empirical locus on PT Gitra Sandi Borlak, using the Balanced Scorecard (BSC) framework. The security outsourcing industry faces structural challenges in the form of high employee turnover rates, discipline issues in the field, and demands for the speed of fulfillment of Service Level Agreements (SLAs) for personnel substitution from corporate clients. Through an analytical descriptive qualitative method that integrates operational data with qualitative in-depth interview data with top management and operational users, this study explores causal relationships across four BSC perspectives. The results of the analysis show that operational problems at the customer level are rooted in the need to reconstruct the pillars of the Learning and Growth Perspective, especially related to human capital retention and standardization of the compensation system. The strategic recommendations are directed at the digitization of GPS-based real-time patrol monitoring and the restructuring of the ongoing coaching program to reduce turnover below the critical tolerance threshold of 10% per annum to secure long-term financial profitability stability.